Understanding The Geology of Bukit Tinggi, Pahang Through Geophysical Study - Binti Mohd Azli, Nadiah (Universiti Teknologi PETRONAS, 2016)
Bukit Tinggi area is located near the Pahang – Selangor boundary and is situated on a big fault zone, known as Bukit Tinggi Fault Zone and comprises of two main lithologies; plutonic igneous rock and metamorphic rock. The plutonic igneous rock in this area is mainly S-type granite and is part of the Main Range Granite while the metamorphic rock is categorized as series of schist and granitic gneiss. The Bukit Tinggi Fault Zone was formed by dextral strike-slip faulting that occurred in Jurassic – Creataceous and later reactivated to sinistral strike-slip fault in Mid to Late Cretaceous. Thirteen small earthquakes were recorded in this area from November 2007 to January 2008 with magnitude of 2.0 to 3.5. Thus, this study is aimed to see the lineament orientations after these several earthquake occurences and to examine the relationship of lineaments of Bukit Tinggi Fault Zone observed on megascale from DEM data and the lineament orientations on mesoscale from magnetic study as well as from structural analysis. One geological fieldwork and one geophysical fieldwork were conducted in Bukit Tinggi area for this project. Six outcrops in Bukit Tinggi and four outcrops in Janda Baik were studied during the geological fieldwork. In Bukit Tinggi area, the igneous rocks were felsic with medium to coarse-grained biotite porphyritic granite and granite gneiss while in Janda Baik, it showed that the granite consisted of fine-grained biotite minerals. Structural analysis was done at the outcrops to interpret the lineament orientations to understand the direction of stress that caused the deformations. Magnetic survey was conducted at Kampung Bukit Tinggi during the geophysical fieldwork to map the lineaments of this area. Eight loops were done, which covered an area of approximately 500m x 500m. The magnetic data was processed and mapped in Surfer 11 software for interpretation. In megascale study, DEM interpretation on the lineaments was done, from Bukit Tinggi area to eastern Selangor. The results obtained from all three methods; outcrop studies, DEM interpretation and magnetic study showed the same lineament orientations with NW-SE major trend and NE-SW as well as E-W minor trends, which followed the regional trend of Bukit Tinggi Fault Zone. However, the magnetic data only showed the NW-SE trend due to limited survey coverage because of inaccessible area of thick vegetation and high hills as well as safety issues.